Association between dietary vitamin B6 intake and endometriosis risk: evidence from the national health and nutrition examination survey - Yin, Ling; Liang, Feng; Xie, Baoli; Su, Yanlin; Cheng, Li; Wei, Xin; Tian, Wencai (Frontiers in Nutrition, 2024)
Background: Endometriosis is a multifaceted disorder with genetic, immune, inflammatory, and multifactorial origins. Vitamin B6 serves as a pivotal coenzyme in various metabolic pathways involving lipids, hemes, nucleic acids, proteins, and carbohydrates. Dysregulation or deficiency of vitamin B6 can perturb human physiology. However, the relationship between dietary vitamin B6 and endometriosis remains elusive. This study aimed to explore the association between dietary vitamin B6 intake and endometriosis. This study aims to explore how dietary intake of vitamin B6 is associated with the risk of endometriosis.Methods: Using cross-sectional data from the National Health and Nutrition Examination Survey, we analyzed information from American women aged 20-54 years between 20011999 and 2006. After adjusting for relevant covariates, multivariable logistic regression analysis was employed to evaluate correlations.Results: A total of 4453 women were included in the study. The multiple linear regression model revealed a positive association between dietary vitamin B6 intake and the risk of endometriosis, even after controlling for confounding variables. Compared to individuals with lower vitamin B6 consumption (Q1: <0.9384 mg/day), the adjusted odds ratio (OR) values for dietary vitamin B6 intake and endometriosis in Q2 (0.9395-1.3859 mg/day), Q3 (1.38640-1.9859 mg/day), and Q4 (>1.9850 mg/day) were 1.212 (95% CI: 0.88-1.679, p = 0.234), 1.242 (95% CI: 0.986-1.713, p = 0. 271879), and 1.531 (95% CI: 1.091-2. 214, p = 0.01804), respectively.Our findings suggest a positive correlation between endometriosis and dietary vitamin B6 intake. Further investigations are imperative to establish a causal relationship between dietary vitamin B6 intake and endometriosis.